Socioeconomic Determinants of Pulmonary Tuberculosis during Covid-19 Pandemic: Case Control Study - M. Umer Abdullah, Amna Imran, Amna Saulat, Fatima Asmat, Saleha Nadeem, M. Ramzan, M. A. Hassan Rafique, R. Rafique, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Tuberculosis (TB) is a public health issue of paramount importance. Pakistan ranks 5th amongst the high burden TB countries globally with the prevalence, incidence and mortality per 100,000 population per year from TB being 348, 276 and 34 respectively. Socio-economic determinants like income, house, family size, ventilation, etc. play a vital role in the epidemiology of TB. Aim: To analyzes the socioeconomic determinants of pulmonary tuberculosis (PTB) during Covid-19 pandemic. Study Design: Case study Methodology: This case-control study was undertaken at Gulab Devi Hospital, Lahore, over a period of 8 months. 50 cases of confirmed Pulmonary tuberculosis and 50 controls were interviewed using a questionnaire containing demographic variables like gender, age, and socioeconomic status. Data was analyzed by using SPSS Results: The sociodemographic profile of our respondents showed that 62 (62%) were males, 55 (55%) belonged to rural areas and, 52(52%) were employed. The socioeconomic determinants which were significantly associated with PTB were gender, residence, occupation, number of family members, and history of smoking. Practical Implementation: Due to the emerging nature of the COVID-19 crisis, this study helped researchers investigate the role of socio-economical determinant of TB during Covid-19 pandemic infection. Conclusion: Gender, residence, occupation, number of family members, and history of smoking were significantly associated with PTB. However, ventilation, family history of TB, and previous history of PTB were not found to have a statistically significant association with PTB. Keywords: Pulmonary Tuberculosis, Covid-19, Incidence, Pandemic Condition and Socioeconomic Determinants.